2004
DOI: 10.1002/jso.20108
|View full text |Cite
|
Sign up to set email alerts
|

Rationale for superficial injection techniques in lymphatic mapping in breast cancer patients

Abstract: One of the most avidly debated issues in lymphatic mapping is where the tracers are best deposited in patients with breast cancer. The four superficial approaches are easy to perform and have several other distinct advantages. They are based on the hypothesis that the entire breast parenchyma and the overlying skin drain to a common node in the axilla because of their common embryological origin. Evidence is presented that casts doubt upon the correctness of this assumption. Tracer administration close to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 24 publications
0
22
1
2
Order By: Relevance
“…The exact site of injection of the mapping agent varies between studies [19][20][21][22][23][24][25] , but can be broadly divided into "superficial" or "deep" 19 . Radioactive colloid is injected preoperatively, with the assistance of radiological imaging either around the tumour, or into the overlying skin.…”
Section: Sentinel Node Methodologymentioning
confidence: 99%
“…The exact site of injection of the mapping agent varies between studies [19][20][21][22][23][24][25] , but can be broadly divided into "superficial" or "deep" 19 . Radioactive colloid is injected preoperatively, with the assistance of radiological imaging either around the tumour, or into the overlying skin.…”
Section: Sentinel Node Methodologymentioning
confidence: 99%
“…The majority of extra-axillary sites were internal mammary lymph nodes, and a few were intramammary or supraclavicular lymph nodes [4][5][6]. Previous studies have reported that the frequency of SN detection depended on the radiocolloid particle size and injection site [13][14][15][16][17][18][19]. The analysis in our institution showed that SN biopsy procedures performed with the intradermal-plus-deep injection method were found to be significantly superior to those involving intradermal injection alone in terms of their ability to detect axillary SN (No.…”
Section: Discussionmentioning
confidence: 99%
“…Tüm bu teknikler aksiller lenf bezi saptamada yeterli olarak bulunmuştur. Yapılan çalışmalarda enjeksiyon metodunun aksiller SLB saptamada fark yaratmadığı bulunmuştur (25). Yüzeyel enjeksiyonların yapılması daha kolaydır.…”
Section: Benjekteedilenaktivitevehacimunclassified